2018
DOI: 10.14507/epaa.26.3690
|View full text |Cite
|
Sign up to set email alerts
|

Title IX coordinators as street-level bureaucrats in U.S. schools: Challenges addressing sex discrimination in the #MeToo era

Abstract: Sex discrimination in educational contexts is an ongoing problem despite the passage of Title IX in 1972. Many schools have not aligned their policies with new laws protecting students from bullying and harassment, and many professionals are unaware of their new obligations in regards to new state regulations. This article presents the findings from semi-structured interviews with 10 participants reporting on the roles and responsibilities of Title IX coordinators in their K-12 school districts. Title IX coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…As mentioned, nearly all the studies assumed a gender binary, and only one of the K-12 empirical studies included a discussion about how Title IX relates to and impacts transgender or gender-nonconforming youth in K-12 schools (Meyer et al, 2018). Brockenbrough (2015) noted that queerness can become invisible if it is not specifically named and attended to.…”
Section: K-12mentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned, nearly all the studies assumed a gender binary, and only one of the K-12 empirical studies included a discussion about how Title IX relates to and impacts transgender or gender-nonconforming youth in K-12 schools (Meyer et al, 2018). Brockenbrough (2015) noted that queerness can become invisible if it is not specifically named and attended to.…”
Section: K-12mentioning
confidence: 99%
“…Only one of the K-12 empirical studies considered the possibilities of Title IX for supporting transgender and gender-nonconforming students. Meyer et al (2018) found that Title IX coordinators in K-12 school districts did not consider transgender and gender-nonconforming students as part of their efforts to comply with Title IX. The researchers found that the Title IX coordinators in this study, though sincere in their desire to do their jobs well, did not understand the scope of Title IX and were generally not provided support and professional development for this role.…”
Section: K-12mentioning
confidence: 99%
“…As we reported in a recently published study (Meyer et al, 2018), our team interviewed Title IX coordinators in districts in California and Colorado and identified four main challenges facing school districts and communities that want to leverage Title IX more effectively to address issues of sex discrimination in their schools. Title IX coordinators, respondents told us, 1) are difficult to find, 2) had ambiguous or overly broad job descriptions and duties, 3) had insufficient training and education, and 4) didn’t understand how their role could support transgender students.…”
Section: Challenges For Title IX Coordinators and School Districtsmentioning
confidence: 99%
“…Whatever the level of funding they choose to allocate to Title IX, all school districts are required at least to appoint a Title IX coordinator. However, evidence suggests that many school systems have failed even to meet this requirement, or they’ve appointed individuals who lack the expertise and support needed to fulfill the role effectively (Equal Rights Advocates, 2015; Meyer et al, 2018).…”
mentioning
confidence: 99%
“…On December 18, the same year, the numbers had gone up to 51,200. While some hits only mention #MeToo in passing as a sign of a changing social context (e.g., Frey & Janssen, 2018; Meyer et al, 2018; Starck & Luyt, 2019; Veissière, 2018), others focus on the #MeToo campaign in its own right (e.g., Hansson et al, 2019). A majority of these take as their point of departure that #MeToo implied a challenge to structures of male dominance, recognizing the effects that the movement had on notions of gender and power.…”
mentioning
confidence: 99%